Dampak Perkembangan Komputer pada Perluasan Arena Garapan Ilmu Fisika - B.Suprapto Brotosiswojo (Indonesian Journal of Physics, 2002)
The dramatic progress in computer technology has inspired physicists to broaden their field of research into several areas. Computing is no longer considered as just a fast, accurate and efficient calculating machine, but also as a thinking tool in their effort to describe and understand the way nature behaves. With its fast logical-inference processing, and its capability to accommodate very large amount of data and memories, physicists are no longer afraid of dealing with complex systems and phenomena, which were usually avoided in the past. On computing itself another concern has surfaced, i.e. an anticipation that the basic elemental processing will have to be carried out on an atomic or subatomic scale. To give an illustration, this article exposes just two examples of progress, namely “Quantum Dot Cellular Automata” and “Quantum Teleportation”. The first example indicates an alternative way of classical computing using quantum dots with a size in the order of hundreds of atomic scale. The second example goes deeply into a real quantum computing, where strange behavior which looks ‘counter intuitive’ actually takes place in nature.